1999
DOI: 10.1023/a:1026614726976
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Following surgical correction of imperforate anus, voluntary bowel control is frequently poor because of abnormal anorectal function. Using colonic manometry we investigated the role of colonic motility in the pathogenesis of fecal soiling in children following imperforate anus repair. Thirteen children with repaired imperforate anus and fecal soiling underwent motility testing 2-12 years after anoplasty. All had fecal incontinence unresponsive to conventional medical treatment. Colonic manometry was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…We believe that this approach can be temporary in otherwise healthy patients, as it may allow recovery of the colonic dysfunction and eventually discontinue its use, although this has not been studied. The colon manometry has been reported as useful in clinical practice to typify the colonic physiology in defecations disorders in patients with colorectal disorders like Hirschsprung’s disease [8, 9] and imperforate anus[10], to predict ACE outcome [11] and to guide surgical therapy in refractory constipation. [12, 13] However, the diagnostic value of the CM to predict outcomes has not been properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this approach can be temporary in otherwise healthy patients, as it may allow recovery of the colonic dysfunction and eventually discontinue its use, although this has not been studied. The colon manometry has been reported as useful in clinical practice to typify the colonic physiology in defecations disorders in patients with colorectal disorders like Hirschsprung’s disease [8, 9] and imperforate anus[10], to predict ACE outcome [11] and to guide surgical therapy in refractory constipation. [12, 13] However, the diagnostic value of the CM to predict outcomes has not been properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, new data has been obtained regarding other pediatric groups, such as repaired anorectal malformations (ARM), Hirschsprung's disease, spinal abnormality and cerebral palsy. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Four studies reported colonic manometry results in children with repaired ARM. 15 , 16 , 17 , 18 Colonic manometry was utilized to investigate the pathophysiology of post‐operative bowel dysfunction 15 , 16 , 18 and evaluated as a tool to predict the outcome of subsequent surgical intervention (cecostomy placement). 17 Study characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies performed colonic manometry using water‐perfused catheters, with four to eight sensors spaced at 10–15 cm intervals. 15 , 16 , 17 Burjonrappa et al 18 did not report the colonic manometry equipment utilized. Colonic manometry specifications are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation